Lower Glutathione Peroxidase Serum Level Compared to Normal Pregnancy - Kadek Pramarta (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To determine the difference of glutathione peroxidase (GPx) in threatened miscarriages and normal pregnancy. Method: This is an analytic cross sectional study with 42 samples divided into two groups. Group 1 consists of 21 cases of threatened miscarriages with < 20 gestational age and group 2 is divided into 21 normal pregnancies of < 20 weeks gestational age. We took 3 cc of blood samples from the cubiti veins and mixed it with EDTA. Its GPx quantities were than examined at the Pathology Lab at Sanglah General Hospital. Data was then analyzed using the Shapiro Wilk Test and the independent t-test with p < 0.05. Result: From this research, we obtained the mean GPx levels on the threatened miscarriages was 49.92 Â± 14.17 U/g Hb lower than the mean of normal pregnancy levels, which was 88.94 Â± 30.11 U/g Hb. Conclusion: The quantities of GPx between threatened miscarriages and normal pregnancies are statistically different, in which the quantity of GPx in threatened miscarriages is lower compared to normal pregnancy. [Indones J Obstet Gynecol 2012; 36-3: 112-5] Keywords: GPx, normal pregnancy, threatened miscarriages